2013
DOI: 10.1007/s00432-013-1509-y
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of neoadjuvant chemotherapy before surgery predicts favorable prognosis for cervical cancer patients: a meta-analysis

Abstract: This meta-analysis confirms that response to NAC is an indicator for PFS and OS, and suggests that patients-achieving response of NAC before surgery predicts favorable prognosis for cervical cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 23 publications
5
26
0
1
Order By: Relevance
“…Scholars (Xiong and colleagues) in Sun Yat-Sen University demonstrated that non-responders had relatively lower survival rates than responders [21]; others (Li and colleagues at Chongqing Medical University; Chen and colleagues at Wuhan University) also made the similar discovery [22, 23]. This study also validated other researchers’ findings as well as our previous results [19, 2124]. Thus, we believe that early clinical response to chemotherapy can be treated as an indicator to DFS.…”
Section: Discussionsupporting
confidence: 89%
“…Scholars (Xiong and colleagues) in Sun Yat-Sen University demonstrated that non-responders had relatively lower survival rates than responders [21]; others (Li and colleagues at Chongqing Medical University; Chen and colleagues at Wuhan University) also made the similar discovery [22, 23]. This study also validated other researchers’ findings as well as our previous results [19, 2124]. Thus, we believe that early clinical response to chemotherapy can be treated as an indicator to DFS.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, this finding is validated by a meta-analysis where Ye et al . pooled data from 18 studies and reported that the response to NACT was significantly associated with better survival outcomes [37]. The largest study that assessed the long-term benefits of NACT was conducted by Alessandro et al .…”
Section: Discussionmentioning
confidence: 99%
“…For patients with LACC, achieving optimal pathological response on surgical specimen is a strong predictor of good clinical outcome 36, 37. The study by Alessandro et al.…”
Section: Discussionmentioning
confidence: 99%